Findings of the Association for Computational Linguistics: ACL-IJCNLP 2021 2021
DOI: 10.18653/v1/2021.findings-acl.315
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Relation between Offensive Language and Mental Health

Abstract: In this paper, we analyze the interplay between the use of offensive language and mental health. We acquired publicly available datasets created for offensive language identification and depression detection and we train computational models to compare the use of offensive language in social media posts written by groups of individuals with and without self-reported depression diagnosis. We also look at samples written by groups of individuals whose posts show signs of depression according to recent related st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Birnbaum et al (2020) found that depressed individuals use more swear words in their Facebook messages compared to controls. Bucur et al (2021b) apply offensive language identification techniques and show that users with depression diagnosis use more offensive language in their Reddit posts, individuals manifesting signs of depression in their posts having a more profane language and fewer insults targeted towards other individuals or groups.…”
Section: Related Workmentioning
confidence: 99%
“…Birnbaum et al (2020) found that depressed individuals use more swear words in their Facebook messages compared to controls. Bucur et al (2021b) apply offensive language identification techniques and show that users with depression diagnosis use more offensive language in their Reddit posts, individuals manifesting signs of depression in their posts having a more profane language and fewer insults targeted towards other individuals or groups.…”
Section: Related Workmentioning
confidence: 99%
“…Even if many works exploring the social media discourse of people diagnosed with depression (Orabi et al, 2018;Burdisso et al, 2019;Uban and Rosso, 2020;Bucur et al, 2021c) are paying attention to the emotions expressed in their social media discourse (Aragon et al, 2021;Lara et al, 2021;Howes et al, 2014), to the best of our knowledge, works focusing on happiness felt by individuals diagnosed with depression are missing. Therefore, we aim to fill this gap and explore the happy moments from the online discourse of users with depression in comparison with control users.…”
Section: Related Workmentioning
confidence: 99%
“…OLID dataset It was the official dataset of the SemEval-2019 Task 6: Identifying and Categorizing Offensive Language in Social Media (OffensEval 2019) (Zampieri et al, 2019b) and SemEval-2020 Task 12: Multilingual Offensive Language Identification in Social Media (OffensEval 2020) (Zampieri et al, 2020). The dataset was also used in misogyny (Pamungkas et al, 2020), cyberbullying (Aind et al, 2020) and depression (Bucur et al, 2021b) research. It contains 14,100 tweets with a hierarchical annotation taxonomy with three levels: Level A -Offensive language identification (offensive vs non-offensive), Level B -categorization of Offensive language (targeted insults or threats vs untargeted profanity) and Level C -Offensive language target identification (individual vs group vs other).…”
Section: Language Example Raw Example Goldmentioning
confidence: 99%